(untitled) (American Journal of Business Management, Economics and Banking, 2024)
In recent years, Muslim countries have accumulated a significant amount of finances. In order to attract them to the economy of Uzbekistan, it is necessary to make some amendments to the legislation to create conditions for the development of Islamic banking.